Demography factors influencing Indonesian general knowledge on COVID-19 - Violantina Linardi; Rizma Adlia Syakurah; Jesica Moudy (Intelektual Pustaka Media Utama, 2021)
Pandemic COVID-19 is a health problem that is spread all over the world including Indonesia. As 4 June 2020, Indonesia has reached 28,818 persons confirmed COVID-19, 1,721 deaths related to COVID-19 and 8.892 patients have recovered from the disease. The amount of response and attention of the public regarding the COVID-19 case in Indonesia and the circulation of information in the community became the basis of interest in identifying and analyzing demography factors with general knowledge on COVID-19. Participants were 1,254 collected through online questionnaire distributed on social media platform, from February 5, 2020 to June 6, 2020. Data analyzed used Chi square test with significant <0.05. The result showed that majority of respondents have good general knowledge about COVID-19 and the personal prevention towards the disease (>75%). Nonetheless, most misinformation was that COVID-19 killed everyone contracted to it, came from a biological weapon laboratory, and that covering mouth and nose with bare hand is considered as correct coughing ethic. Characteristics that showed statistical significances were education, occupation, and educational/occupational background. Although Indonesian governments already give the best effort to educate the public to stop the transmission, an extensive educational health campaign should be done to raise awareness in public about preventive knowledge and behavior of COVID-19.